Implementasi Manajemen Stratejik dalam Meningkatkan Literasi Dan Numerasi Siswa Di SD Negeri Balibunga Kota Tidore Kepulauan - Nur, Nahrudin M; Apriyani, Apriyani; Ramli, Nurdela; Batidas, Theresia (Universitas Pendidikan Indonesia (UPI), 2025)
The study entitled the implementation of strategic management toimprove literacy and numeracy at the elementary school level aimsto determine whether elementary schools (SD) have implementedactivity programs to improve literacy and numeracy in elementaryschools, this study uses a qualitative approach with a descriptiveapproach in order to dig deeper into issues related to theimplementation of strategic management in decision making inelementary schools, the purpose of this study is to see theimplementation of strategic management used by schoolprincipals in improving literacy and numeracy, interviews,documentation and also observation results are methods used todig research data, in addition, literature studies are also used in theform of studies of several previous research journals to see gaps inresearch, books and mass media, research related to literacy andnumeracy needs to be and continues to be encouraged in easternIndonesia considering the educational gap with western Indonesiais too far